# If α,β,γ are the roots of x3+qx+r=0 then the equation whose roots β/γ+γ/β,γ/α+α/γ,α/β+β/α is

1.  x3-q2x2-2qr2x-r4=0

2.  rx3+q(1-r)x2+ (1-r)3=0

3.  x3-2qx2+q2x+r2=0

4.  r2x3+3r2x2+  (3r2+q3) x + 2q3+r2=0

4
Correct Answer :

r2x3+3r2x2+  (3r2+q3) x + 2q3+r2=0

Explanation :
No Explanation available for this question

1.  continuous

2.  discontinuous

3.  not determined

4.   none

4
Correct Answer :

Explanation :
No Explanation available for this question

# If α,β,γ are the roots of x3+2x+5=0 then the equation whose roots βγ+1/α,γα+1/β,αβ+1/γ is

1.  5x3+8x2+64=0

2.  5x3+-x2+64=0

3.  5x3-8x2-64=0

4.  5x3+8x2-64=0

4
Correct Answer :

5x3-8x2-64=0

Explanation :
No Explanation available for this question

1.  continuous

2.  discontinuous

3.  not determined

4.   none

4
Correct Answer :

discontinuous

Explanation :
No Explanation available for this question

# If α,β,γ are the roots of x3+3x+4=0 then the equation whose roots β/γ+γ/β,γ/α+α/γ,α/β+β/α is

1.  16x3+48x2+75x+70=0

2.  16x3-48x2+75x+70=0

3.  16x3-48x2-75x+70=0

4.  16x3-48x2+75x-70=0

4
Correct Answer :

16x3+48x2+75x+70=0

Explanation :
No Explanation available for this question

1.  continuous

2.  discontinuous

3.  not determined

4.  none

4
Correct Answer :

continuous

Explanation :
No Explanation available for this question

# If α,β,γ are the roots of x3+qx+r=0 then the equation whose roots (β – γ)2,(γ – α)2,(α – β)2 is

1.  x3+6qx2+9q2x+4q3+27r2=0

2.  x3+2qx2+9q2x+4q3+27=0

3.  x3+3qx2+6q2x+2q3+27r2=0

4.  x3+qx2+3q2x+6q2+27=0

4
Correct Answer :

x3+6qx2+9q2x+4q3+27r2=0

Explanation :
No Explanation available for this question

1.  continuous

2.  discontinuous

3.  not determined

4.  none

4
Correct Answer :

discontinuous

Explanation :
No Explanation available for this question

1.  continuous

2.  discontinuous

3.  not determined

4.  none

4
Correct Answer :

discontinuous

Explanation :
No Explanation available for this question

# If α,β,γ are the roots of x3+qx+r=0 then the equation whose roots βγ+1/α,γα+1/β,αβ+1/γ is

1.  x3-q2x2-2qr2x-r4=0

2.  rx3+q(1-r)x2+ (1-r)3=0

3.  x3-2qx2+q2x+r2=0

4.  r2x3+3r2x2+  (3r2+q3) x + 2q3+r2=0

4
Correct Answer :

rx3+q(1-r)x2+ (1-r)3=0

Explanation :
No Explanation available for this question

## Interview Questions

 MongoDB Java Script Node JS PHP JQuery Python